Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix B - Graphs of Equations - Exercises - Page 427: 48

Answer

Refer to Graph I, Center of the circle = $(-1, -2)$ Radius = $\frac{2 – (-4)}{2}$ = $3$ The center-radius form of the circle equation is $(x + 1)^2$ + $(y + 2)^2$ = $9$
1498130827

Work Step by Step

Refer to Graph I, Center of the circle = $(-1, -2)$ Radius = $\frac{2 – (-4)}{2}$ = $3$ The center-radius form of the circle equation is $(x – (-1))^2$ + $(y – (-2))^2$ = $3^2$ $(x + 1)^2$ + $(y + 2)^2$ = $9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.